Association between dietary patterns and existing natural teeth in Chinese elderly: a national community-based study - Huang, Deng; Ding, Pan; Lin, Chao; Tian, Liuhong; Kuang, Xiaodan; Fang, Jiaming; Chen, Shulei; Ding, Rongxiu (Frontiers in Nutrition, 2025)
ObjectiveTo promote healthy aging, we aimed to evaluate the independent and joint effects of protein, sugar-salt, and anti-inflammatory diets on existing natural teeth among the Chinese elderly, and further explore the mediating role of body mass index (BMI).MethodsBased on the 2017–2019 Chinese Longitudinal Healthy Longevity Survey (CLHLS), 11,608 participants aged 65 and above were recruited in this cross-sectional study. Protein, sugar-salt, and anti-inflammatory diets were measured via a simplified 13-item dietary frequency questionnaire (dietary frequency around age 60). Restricted cubic spline and multiple linear regression analyses evaluated associations between dietary patterns and existing natural teeth, and mediation analysis explored BMI’s role.ResultsProtein and anti-inflammatory diets were positively and linearly associated with existing natural teeth, while sugar-salt diets were negatively and linearly associated. Compared with the low dietary patterns (Q1), high protein and anti-inflammatory diets (Q4) were associated with a higher number of teeth (β: 1.70, 95%CI: 1.14, 2.25; β: 1.98, 95%CI: 1.45, 2.51, respectively; and 28% and 38% risk decreased for fewer than 20 teeth, respectively), whereas high sugar-salt diets had the lowest number (β: −1.14, 95%CI: −1.61, −0.67; 44% risk increased for fewer than 20 teeth). We further found a joint effect of low protein, high sugar-salt, and low anti-inflammatory diets on existing natural teeth (β: −1.97, 95% CI: −2.61, −1.33). Moreover, BMI mediated 10.88%, 19.69%, and 10.74% of the effects of the protein, sugar-salt, and anti-inflammatory diets with existing teeth, respectively.ConclusionPromoting high protein and anti-inflammatory diets and reducing sugar-salt intake in elderly individuals may reduce tooth loss, possibly partly mediated through overweight or obesity.